Case Report: Sulcal artery infarction presenting as incomplete Brown-Séquard syndrome following spinal anesthesia in a 70-year-old female: a rare postoperative neurological complication - Kavya, B. T.; Poojary, Shweta Raviraj; Sundaramurthy, Harsha (Frontiers in Radiology, 2025)
Spinal cord infarction following neuraxial anesthesia is a rare but serious complication. We present the case of a 70-year-old female who developed acute onset of left lower limb weakness immediately following spinal anesthesia administered for total hip replacement. Clinical features were consistent with incomplete Brown-Séquard syndrome. MRI revealed a T2/STIR hyperintense lesion involving the left hemicord at the D12-L1 vertebral level, suggestive of sulcal artery infarction. MRI showed only age-related changes. After a structured physiotherapy program, the patient experienced significant functional improvement and was discharged with stable vitals. This case highlights the importance of early diagnosis and management of spinal cord infarction in the perioperative setting.